Ibnu Taimiyah’s Perspective on The Mimbaan Traditional Market Mechanism in Situbondo - Isvina Vawaidatur Rohmah; Lilik Rahmawati; Iffah Febri Anti Fitriyatul L (Universitas Darussalam Gontor, 2023)
The market mechanism is a process of forming prices based on the forces of supply and demand. At the Mimbaan traditional market in Situbondo City, the current price formation is not only influenced by changes in demand and supply, but there are other factors that influence it. Including influenced by imperfect competition. So that there is a market price game that results in price instability. However, according to Ibn Taimiyah, price formation comes from the balance of supply and demand. Consumers and producers are the main factors in the market mechanism, especially in price formation. The purpose of this research is to know the market mechanism according to Ibnu Taimiyah, to know the market mechanism in the Mimbaan traditional market in Situbondo City, and to analyze the market mechanism in the Mimbaan traditional market market in Situbondo City based on the opinion of Ibnu Taimiyah. The research was conducted using qualitative methods, and the data obtained was based on data collection through interviews. Data analysis techniques carried out in this study used descriptive analysis methods. The results of the study show that there is a discrepancy between the market mechanism of the Mimbaan traditional market in Situbondo City and the market mechanism according to Ibnu Taimiyah. However, there are also several things that are in accordance with Ibn Taimiyah's opinion regarding price fixing. By applying Ibn Taimiyah's opinion to the current market mechanism, it can help maintain the stability of the market price of an item and prevent imperfect market mechanisms from occurring.